Evolution of nest architecture in tyrant flycatchers and allies - Ocampo, David; De Silva, Thilina N; Sheard, Catherine; Stoddard, Mary Caswell (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2023)
Innovations in nest design are thought to be one potential factor in the evolutionary success of passerine birds (order: Passeriformes), which colonized new ecological niches as they diversified in the Oligocene and Miocene. In particular, tyrant flycatchers and their allies (parvorder: Tyrannida) are an extremely diverse group of New World suboscine passerines occupying a wide range of habitats and exhibiting substantial extant variation in nest design. To explore the evolution of nest architecture in this clade, we first described nest traits across the Tyrannida phylogeny and estimated ancestral nest conditions. We then quantified macroevolutionary transition rates between nest types, examined a potential coevolutionary relationship between nest type and habitat, and used phylogenetic mixed models to determine possible ecological and environmental correlates of nest design. The Tyrannida ancestor probably built a cup nest in a closed habitat, and dome nests independently evolved at least 15 times within this group. Both cup- and dome-nesting species diversified into semi-open and open habitats, and we did not detect a coevolutionary relationship between nest type and habitat. Furthermore, nest type was not significantly correlated with several key ecological, life-history and environmental traits, suggesting that broad variation in Tyrannida nest architecture may not easily be explained by a single factor. This article is part of the theme issue 'The evolutionary ecology of nests: a cross-taxon approach'.